THE URGENCY OF RATIFYING THE DRAFT LAW ON INDIGENOUS COMMUNITIES AS LEGAL PROTECTION FOR INDIGENOUS COMMUNITIES IN INDONESIA - Putri, Shevanna (Zhata Institut, 2024)
This research is conducted to obtain recognition and protection of the rights of indigenous communities by striving for the ratification of the Draft Law on Indigenous Communities. This research employs a normative juridical approach based on secondary data, including primary and secondary legal data obtained through literature review. The research approach used is statutory and conceptual approach to the problem discussed. The research findings indicate that the impact of the non-ratification of the Draft Law on Indigenous Communities could lead to legal uncertainty for indigenous communities, particularly regarding customary land which is often contested by parties with economic or developmental interests. Regulatory ambiguity frequently results in conflicts between customary law and positive law or modern regulations enforced by the government. Therefore, the enactment of the Draft Law on Indigenous Communities could serve as a legal umbrella providing certainty and legal protection for indigenous communities, thereby contributing to the implementation of one of Indonesia's national goals.